Peran Advokat sebagai Pendamping Hukum Dalam Memberikan Bantuan Hukum terhadap Masyarakat yang Tidak Mampu secara Sukarela - Lara Nopi Dayanti; Aulia Nisma; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
In an effort to realize the role of an advocate as a legal assistant as well as a protector of the human rights of every human being whose function is to provide free legal assistance to underprivileged people, an advocate should have thoroughly administered the law without discriminating against the person's background. So that everyone will be equal before the law. Advocates are law enforcers who are free, independent and responsible for enforcing the law whose existence is guaranteed by law. This shows that advocates have rights, obligations and responsibilities in accordance with the laws and regulations of advocates. In Law Number 18 of 2003 concerning Advocates, it is stated that an Advocate is a person whose profession is providing legal assistance, both in court and outside the Court. What is meant by legal services are services provided by an advocate, namely in the form of providing legal consultations/negotiations, legal assistance, accompanying clients, defending and carrying out legal actions for the benefit of their clientsAn advocate must carry out his duties and professional oath for the sake of upholding justice based on law for the benefit of people who seek justice, including in terms of teaching people about their fundamental rights before the law. In the Advocate oath of profession, Advocates are required to provide legal assistance to people who cannot afford it for free.Therefore advocates need state intervention in it in order to enforce the law as a whole. However, what is currently happening is how to make legal aid not only for the rich but also for the poor. Keywords: Responsibility, Advocate, Legal Aid